The Holocaust Trauma and Autobiographism in Ida Fink’s and Charlotte Delbo’s Stories - Anastasiia Mikhieieva (Kyiv-Mohyla Humanities Journal)
The research is based on a study of short story collections by Israeli writer Ida Fink’s, All the Stories, and French writer Charlotte Delbo’s, Auschwitz and After, to reflect the impact of the Holocaust on autobiographical elements in their work. The authors are representatives of the first generation of Holocaust survivors, which means that the mass systematic genocide during World War II was a personal traumatic experience for them. The works of female writers are studied using the theory of trauma at the genre level. Since autobiography has been considered a documentary genre with its own peculiarities, works about the Holocaust were seen as historical evidence of this event. However, based on the works of Juri Lotman and some principles of Philippe Lejeune’s “autobiographical pact”, we can conclude that autobiography is similar to fiction if it can meet certain aesthetic functions. Under the influence of trauma, the genre of autobiography can be modified in the literary text in such a way that the line between autobiography and fiction is blurred. Ida Fink and Charlotte Delbo write short stories with fictional narrators, but all the situations are certainly the experiences of the writers themselves, who turn to the autofiction and conventions of Philippe Lejeune’s “autobiographical pact” to transfer their memories to literary heroes. The aim of the study is to define the peculiarities of the autobiographical genre, analyze its functions in Holocaust literature, identify poetic elements of autobiography, and prove that there is no canonical form of narration about the Holocaust-Era, as the writers were searching for how to articulate their traumatic experience in experimental forms.